Simplifying the audit of risk factor recording and control: A report from an international study in 11 countries. (July 2016) - Zhao, Min; Cooney, Marie Therese; Klipstein-Grobusch, Kerstin; Vaartjes, Ilonca; De Bacquer, Dirk; De Sutter, Johan; Reiner, Željko; Prescott, Eva; Faggiano, Pompilio; Vanuzzo, Diego; AlFaleh, Hussam; Menown, Ian BA; et al.
Background: To simplify the assessment of the recording and control of coronary heart disease risk factors in different countries and regions. Design: The SUrvey of Risk Factors (SURF) is an international clinical audit. Methods: Data on consecutive patients with established coronary heart disease from countries in Europe, Asia and the Middle East were collected on a one-page collection sheet or electronically during routine clinic visits. Information on demographics, diagnostic category, risk factors, physical and laboratory measurements, and medications were included and key variables summarized in a Cardiovascular Health Index Score. Results: Coronary heart disease patients ( N = 10, 186; 29% women) were enrolled from 79 centres in 11 countries. Recording of risk factors varied considerably: smoking was recorded in over 98% of subjects, while about 20% lacked data on laboratory measurements relevant to cardiovascular disease risk. Sixteen per cent of participants reported smoking, 29% were obese, and 46% had abdominal obesity. Sixty per cent of participants had blood pressure <140/90 mmHg (140/80 mmHg for diabetics), 48% had HbA1c<7%, 30% had low-density lipoprotein <1.8 mmol/l and 17% had a good cardiovascular health index score. There were substantial regional variations. Less than 3% of patients attended cardiac rehabilitation in Asia or the Middle East, compared with 45% in Europe. In Asia, 15% of patients had low-density lipoprotein cholesterol <1.8 mmol/l compared with 33% in Europe and 36% in the Middle East. Variations in medications were noted, with lower use of statins in Asia. Conclusions: SURF proved to be practical in daily practice. Results indicated poor control of risk factors with substantial variation between countries, calling for development and implementation of clinical standards of secondary prevention of coronary heart disease.